The impact of internet and social media on the habit of reading books: A case study in the southern region of Bangladesh - Md. Obaidullah; Molla Azizur Rahman (Studies in English Language and Education, 2018)
This study tries to find out the influence of Internet and social media on students’ habit of reading printed books. The entire study is conducted among a sample of 96 students of two different institutions of Khulna, a southern district of Bangladesh. Primary data are collected through a questionnaire survey where the number of variables is 16. The study tries to explore that students are less interested in reading books and are prone to gather information through passive sources like movies, television, the Internet, etc. The result shows that students spend more hours on electronic media than on reading books. They take more pleasure in technology or social media than reading books. So, this study tries to bring the present vulnerable condition of reading habit into light.